The Effectiveness of Chain writing Learning Method on Student's Writing Skills - Yudi Utami, Yulistya Putri; Wahidiyati, Irra (ELITE JOURNAL, 2025)
Chain writing is one of the learning methods that can help students in the classroom with collaborative techniques. Chain writing is implemented through learning activities and games. This research is used to find out how effective the use of chain writing learning method at 9th grade of MTs Ma’arif NU 1 Cilongok. This research is using quasi-experiment method. The sample chosen in this study was random sampling because it used quasi-experimental methods. The population of this study was 194 students. The data collection techniques used pre-test and post-test for experiment class and control class. The data analysis technique used normality test, homogenity test and hypothesis test. Based on the research data, there are differences in the results in the experimental class using the chain writing learning method with the control class that does not use this method. The different effect in students writing skill between using chain writing learning method and without using chain writing learning method is evidenced by the hypothesis test which shows assymp. Sig. (2-tailed) is 0.000 (0.000 < 0.05) This means that H0 was rejected and Ha was accepted. Based on this statement, it can be concluded that the chain writing learning method is quite effective to improve students' writing skills.